2016
DOI: 10.1080/02688697.2016.1270419
|View full text |Cite
|
Sign up to set email alerts
|

Gross total resection rates of grade II/III intramedullary ependymomas using the surgical strategy of en-bloc resection without intra-operative neurophysiological monitoring

Abstract: The current series with a GTR of 94.12% compares favourably with other published series with GTRs of 55.8-84% with no significant difference in functional outcomes. Series with low GTRs should examine their operative strategy or false-positive alarm rates which may lead to higher STRs. This series should be viewed as a unique opportunity to benchmark GTRs of circumscribed intramedullary tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…We found that IONM was used in 80% and was missing in 10 cases with intramedullary tumors. This is in line with recently published data on use (46) or non-use of IONM (47). At our institution, one senior neurophysiologist attends all surgeries with IONM.…”
Section: Discussionsupporting
confidence: 92%
“…We found that IONM was used in 80% and was missing in 10 cases with intramedullary tumors. This is in line with recently published data on use (46) or non-use of IONM (47). At our institution, one senior neurophysiologist attends all surgeries with IONM.…”
Section: Discussionsupporting
confidence: 92%
“…Further efforts are required to identify the most valid and reliable parameters that can guide surgery and predict led to a GTR rate of 94,12% (43), which is very similar to the rate we achieved.…”
Section: █ Conclusionsupporting
confidence: 72%
“…25 Oh et al reported in their meta-analysis no difference in OS or PFS between MPE and grade II ependymoma. 15 Weber et al demonstrated a treatment failure rate of 33% in their series. 26 Surgically, this may be explained by the complexity of these lesions, which can be densely adherent, even appearing to be infiltrating the conus medullaris and/or cauda equina, making GTR in conjunction with neurologic preservation technically challenging.…”
Section: Intramedullary Spinal Cord Ependymomamentioning
confidence: 99%
“…14 The ability to achieve GTR for intramedullary grade II ependymomas can be as high as 93% while being safely performed in most patients. [15][16][17] GTR is facilitated in characteristically well-defined and encapsulated World Health Organization (WHO) Grade I tumors; however, this is less likely in infiltrative grade II and the more aggressive grade III ependymomas. 18 Whenever possible, intramedullary ependymomas should be removed en bloc, as piecemeal removal may facilitate CSF dissemination.…”
Section: Intramedullary Spinal Cord Ependymomamentioning
confidence: 99%